1997
DOI: 10.1007/bf02305554
|View full text |Cite
|
Sign up to set email alerts
|

Pleural lavage cytology immediately after thoracotomy and before closure of the thoracic cavity for lung cancer without pleural effusion and dissemination: Clinicopathologic and prognostic analysis

Abstract: PLC status after thoractomy provides useful information in the detection of high-risk subgroup for pleural recurrence. Although PLC status is closely associated with survival, its prognostic value is not independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 8 publications
2
41
2
Order By: Relevance
“…In Asian countries, the predominant histological type of esophageal carcinoma is squamous cell carcinoma, and tumors are frequently located in the thoracic esophagus. As in lung cancer (11)(12)(13)(14), the presence of exfoliated cancer cells in the pleural cavity after The results are presented as the means ± SEM. The isotonic NaCl buffer before cell suspension, n=5; the other solutions, n=3.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian countries, the predominant histological type of esophageal carcinoma is squamous cell carcinoma, and tumors are frequently located in the thoracic esophagus. As in lung cancer (11)(12)(13)(14), the presence of exfoliated cancer cells in the pleural cavity after The results are presented as the means ± SEM. The isotonic NaCl buffer before cell suspension, n=5; the other solutions, n=3.…”
Section: Discussionmentioning
confidence: 99%
“…Spread of malignancies to the pleural cavity, resulting in malignant pleural effusions and pleural metastatic disease are associated with a dismal prognosis, with most patients surviving only a few months after the diagnosis is made (40)(41)(42)(43)(44)(45)(46)(47). While NSCLC is the most common cause of malignant disease of the pleura, the pleural model used in this study is also relevant to other cancer types, including mesothelioma, breast, ovarian, and lymphoid cancers (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Such foci of disease are extremely difficult to diagnose preoperatively. Metastatic disease in the pleural cavity may indicate a more aggressive tumor biology an a higher risk of recurrence (12)(13)(14)(15)(16), which could contribute to the decreased survival often seen in these patients. As such, new techniques are needed to both diagnose and treat metastatic pleural spread of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…9 Briefly, when no malignant findings were noted, the pleural cavity was washed with 200 ml of physiological saline solution, most then collected into a glass bottle with a mixture of heparin. After centrifugation, the sediment was stained using Giemsa, Papanicolaou, and Alcian blue on 8 glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigators, including ourselves, [5][6][7][8][9][10][11][12][13] have reported intraoperative pleural lavage cytology (PLC) -positive lung cancer patients, despite a lack of macroscopic findings of malignant pleuritis at thoracotomy. Overall, 3.7 to 45.7% of operable lung cancer pa- Table I.…”
mentioning
confidence: 99%